2015
DOI: 10.7887/jcns.24.705
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Anatomical Relationships of the Vagus Nerve with Internal Jugular Vein and Common Carotid Artery in the Neck Necessary for Vagus Nerve Stimulation (VNS) Surgery

Abstract: A precise understanding of the anatomy is essential to perform vagus nerve stimulation VNS therapy for refractory epilepsy. We evaluated the anatomical relationships of the cervical vagus nerve with the carotid artery and jugular vein on the basis of findings during VNS surgery. We investigated the anatomical relationships among the vagus nerve VN , common carotid artery CCA , and internal jugular vein IJV in 73 patients who underwent VNS surgery at our hospital from December 2010 to January 2015, classified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The ultrasonographical study demonstrated that vagus nerve variation is seen in 5.5% of 326 cases, and the vagus nerve runs dorsal to the CCA after it changes the course in 1.2% of cases [ 5 ]. Regarding the VNS, a previous study reported that the anatomical relationships between the vagus nerve and the blood vessels, including the IJV and the CCA, are classified into five patterns [ 3 ]. Accordingly, a type in which the vagus nerve is located dorsal to the CCA was seen in 4.1% of 73 cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ultrasonographical study demonstrated that vagus nerve variation is seen in 5.5% of 326 cases, and the vagus nerve runs dorsal to the CCA after it changes the course in 1.2% of cases [ 5 ]. Regarding the VNS, a previous study reported that the anatomical relationships between the vagus nerve and the blood vessels, including the IJV and the CCA, are classified into five patterns [ 3 ]. Accordingly, a type in which the vagus nerve is located dorsal to the CCA was seen in 4.1% of 73 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3D-CTA requires radiation exposure, which can be the biggest disadvantage of this technique. Because previous studies indicated that the vagus nerve location was detectable by ultrasonography [ 3 , 5 , 6 , 7 ], it may be considered to be enough to visualize its location. However, clinical examination of cervical ultrasonography by radiographers is usually not intended to detect the vagus nerve location or clarify the anatomical relationships around the nerve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations